Prodromus of a fern flora for Bolivia. III. Selaginellaceae - Smith, Alan R.; Kessler, Michael (Phytotaxa, 2018)
We provide a synopsis to the lycophyte family Selaginellaceae in Bolivia. The single genus in the family, Selaginella, comprises 36 known species in Bolivia, of perhaps 200+ in the Neotropics. Five species are known only from Bolivia (S. alampeta, S. angustifolia, S. bryophila, S. glossophylla, and S. solomonii), and several others are poorly represented in collections, indicating a need for further studies and additional collections.